Rehabilitation interventions need more than methodological standardisation: an individualised approach. Issue 1 (19th November 2020) - Welch, Neil; Richter, Chris; Moran, Kieran; Franklyn-Miller, Andy
Abstract : Objectives: The main aim in the current study was to use a single-subject analysis to profile the physical performance characteristics of individuals within an injured group and a between-group approach to profile the group as a whole. These profiles were then used to inform single-subject and between-group rehabilitation interventions. Methods: Fifty-three (28 with athletic groin pain and 25 non-injured) Gaelic football players (24.8 years±7.1 years; 179 cm±5.5 cm; 79.7 kg±9.2 kg) underwent 3D biomechanical analysis, which was used to measure a series of physical performance characteristics. The non-injured group was used to create a 'performance database' to compare the injured individuals, and a between-group analysis was also conducted. The scores from each analysis were used to inform the targets of interventions. Results: The analysis highlighted the variety of profiles that existed across the tested individuals and that these profiles differed from that of the between-group analysis. By analysing individuals in a single-subject approach, detail can be seen that is lost with between-group analysis.